MEMBANGUN MOTIVASI KERJA MELALUI BUDAYA ORGANISASI YANG FLEKSIBEL DAN BERORIENTASI MASA DEPAN - Kasih Aulia; Lili Fatmawati; Nafiza Ramadhani; Mutiara Erfares; Natswa Salsabilla; Novia Fadhila; Ferdino Wedi Sanjaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Work motivation is one of the key factors contributing to organizational effectiveness and success. Rapid changes in the work environment, driven by technological advancements, globalization, and the increasing demands of the modern workplace, require organizations to develop an organizational culture that is flexible and adaptable. This study aims to identify the characteristics of a flexible and future-oriented organizational culture, analyze the factors supporting its implementation, and examine its influence on employee work motivation. A flexible and future-oriented organizational culture is considered essential for fostering employee motivation and improving organizational performance. This study employs the Systematic Literature Review (SLR) method by reviewing and analyzing scientific journal articles, books, and previous research related to organizational culture and work motivation. The review process follows the stages of identification, selection, evaluation, and synthesis of relevant literature based on systematic review principles. The findings indicate that the main characteristics of a flexible organizational culture include adaptability to change, open communication, support for innovation, collaboration, and employee empowerment through greater autonomy. A future-oriented organizational culture is reflected in a long-term vision, continuous learning, competency development, and organizational readiness to respond effectively to environmental changes. The successful implementation of this culture is supported by visionary leadership, strong organizational commitment, and continuous human resource development. Furthermore, the review demonstrates that a flexible and future-oriented organizational culture positively influences employee work motivation, enhances engagement, improves productivity, and strengthens organizational competitiveness. Therefore, organizations are encouraged to cultivate an adaptive culture that supports sustainable performance and prepares employees to face future challenges in an increasingly dynamic and competitive business environment. Work motivation is one of the key factors contributing to organizational effectiveness and success. Rapid changes in the work environment, driven by technological advancements, globalization, and the increasing demands of the modern workplace, require organizations to develop an organizational culture that is flexible and adaptable. This study aims to identify the characteristics of a flexible and future-oriented organizational culture, analyze the factors supporting its implementation, and examine its influence on employee work motivation. A flexible and future-oriented organizational culture is considered essential for fostering employee motivation and improving organizational performance. This study employs the Systematic Literature Review (SLR) method by reviewing and analyzing scientific journal articles, books, and previous research related to organizational culture and work motivation. The review process follows the stages of identification, selection, evaluation, and synthesis of relevant literature based on systematic review principles. The findings indicate that the main characteristics of a flexible organizational culture include adaptability to change, open communication, support for innovation, collaboration, and employee empowerment through greater autonomy. A future-oriented organizational culture is reflected in a long-term vision, continuous learning, competency development, and organizational readiness to respond effectively to environmental changes. The successful implementation of this culture is supported by visionary leadership, strong organizational commitment, and continuous human resource development. Furthermore, the review demonstrates that a flexible and future-oriented organizational culture positively influences employee work motivation, enhances engagement, improves productivity, and strengthens organizational competitiveness. Therefore, organizations are encouraged to cultivate an adaptive culture that supports sustainable performance and prepares employees to face future challenges in an increasingly dynamic and competitive business environment.